Concomitant Administration of Vancomycin with a High Dose of Meropenem May Cause Acute Kidney Injury - Yoshiro Sakai; Seiji Karakawa; Takato Koutaki; Kyoko Higuchi; Aya Hashimoto; Hiroshi Watanabe (Case Reports in Infectious Diseases)
Coadministering two different classes of antibiotics as empirical therapy can be critical in treating healthcare-associated infections in hospitals. Herein, we report a case of acute kidney injury (AKI) caused by coadministration of vancomycin with high-dose meropenem that manifested as a rapid increase in serum creatinine levels and an associated increase in vancomycin trough concentrations. The patient was diagnosed with meningioma at 50 years and was followed up regularly. The patient underwent surgery and antibiotic treatment between 63 and 66 years for suspected meningitis and pneumonia. Coadministration of vancomycin with high-dose meropenem (6.0 g/day) caused AKI; however, no AKI occurred when vancomycin was administered alone or with a low dose of meropenem (1.5 or 3.0 g/day). To our knowledge, this report is the first to show that administering different dosages of meropenem in combination with vancomycin may contribute to the risk of developing AKI. We suggest that coadministered vancomycin and high-dose meropenem (6.0 g/day) may increase the risk of AKI. Our report adds to the limited literature documenting the coadministration of vancomycin with varying doses of meropenem and its impact on the risk of AKI and highlights the importance of investigating AKI risk in response to varying dosages of meropenem when it is coadministered with vancomycin.